2012
DOI: 10.1136/bjophthalmol-2011-300581
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome and risk stratification for primary retinal detachment repair: results from the Scottish Retinal Detachment study

Abstract: Consistent with previous series, the overall early success rate of RRD repair was 80% after one operation. The type of surgical repair did not influence overall success rates. Significant predictors of failure are the presence of preoperative proliferative vitreoretinopathy of any grade and the extent of detachment. The analytical value of current classification systems in predicting failure is most useful in complex RRDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
56
0
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 23 publications
10
56
0
6
Order By: Relevance
“…Despite excellent surgical success rates, with an anatomical reattachment reaching up to 94% [1, 2], visual recovery varies after rhegmatogenous retinal detachment (RD). The postoperative quality of vision may be disappointing for both the patient and the surgeon [3].…”
Section: Introductionmentioning
confidence: 99%
“…Despite excellent surgical success rates, with an anatomical reattachment reaching up to 94% [1, 2], visual recovery varies after rhegmatogenous retinal detachment (RD). The postoperative quality of vision may be disappointing for both the patient and the surgeon [3].…”
Section: Introductionmentioning
confidence: 99%
“…In the UK, PPV surgery is currently the dominant technique used to treat RD and SB is increasingly reserved for non-complex RD in the absence of posterior vitreous separation in young patients. 13 In contrast to PPV or SB, combined PPV + SB surgery had the highest rates of failure for all grades of surgeon in our series. Although the number of these cases is relatively small making it difficult to draw firm conclusions, case selection is likely to explain the higher failure rate in this group as this technique is disproportionately used to treat more complex cases.…”
Section: Failure Rate By Technique Of Surgerymentioning
confidence: 86%
“…Significant variation in reported primary RD failure exists. [10][11][12][13][14][15][16][17][18][19] This range may be due to variations in patient selection including surgical complexity, the definition of primary RD failure, the timeframe for reporting failure, and the inclusion or exclusion of cases with silicone oil in situ. A recent nationwide database study from Denmark found a 22% re-operation rate after RD surgery, using a large subset of 6,522 eyes of which 29.5% received silicone oil injection.…”
Section: Failure Rate By Technique Of Surgerymentioning
confidence: 99%
See 2 more Smart Citations